Risks of source and species-specific air pollution for COVID-19 incidence and mortality in Los Angeles - Lin-Syuan Yang; Michael J Kleeman; Lara J Cushing; Jonah Lipsitt; Jason Su; Richard T Burnett; Christina M Batteate; Claudia L Nau; Deborah R Young; Sara Y Tartof; Rebecca K Butler; Ariadna Padilla; et al. (IOP Publishing, 2024)
Growing evidence from ecological studies suggests that chronic exposure to standard air pollutants (PM _2.5 , NO _2 , and ozone) exacerbates risks of coronavirus 2 (COVID-19) incidence and mortality. This study assessed the associations between an expanded list of air pollutants and COVID-19 incidence and mortality in Los Angeles. Annual mean exposure to air pollutants in 2019-including PM _0.1 mass, PM _2.5 mass, PM _2.5 elemental carbon (EC), PM _2.5 tracer from mobile sources, NO _2 , and ozone-were estimated at the ZIP code level in residential areas throughout Los Angeles. Negative binomial models and a spatial model were used to explore associations between health outcomes and exposures in single pollutant and multi-pollutant models. Exposure to PM _0.1 mass, ozone, NO _2 , and PM _2.5 EC were identified as risk factors for COVID-19 incidence and mortality. The results also suggest that PM _2.5 and NO _2 together may have synergistic effects on harmful COVID-19 outcomes. The study provides localized insights into the spatial and temporal associations between species-specific air pollutants and COVID-19 outcomes, highlighting the potential for policy recommendations to mitigate specific aspects of air pollution to protect public health.